Catheter-associated urinary tract infection in a surgical intensive care unit - Mladenović, Jovan Ljubomir; Veljović, Milić; Udovičić, Ivo; Lazić, Srdjan; Jadranin, Željko; Šegrt, Zoran; Ristić, Petar; Šuljagić, Vesna (Vojnosanitetski pregled, 2015)
Background/Aim. Because patients in intensive care units usully have an urinary catheter, the risk of urinary tract infection for these patients is higher than in other patients. The aim of this study was to identify risk factors and causative microrganisms in patients with catheter-associated urinary tract infection (CAUTI) in the Surgical Intensive Care Unit (SICU) during a 6-year period. Methods. All data were collected during prospective surveillance conducted from 2006 to 2011 in the SICU, Military Medical Academy, Belgrade, Serbia. This case control study was performed in patients with nosocomial infections recorded during surveillance. The cases with CAUTIs were identified using the definition of the Center for Disease Control and Prevention. The control group consisted of patients with other nosocomial infections who did not fulfill criteria for CAUTIs according to case definition. Results. We surveyed 1,369 patients representing 13,761 patient days. There were a total of 226 patients with nosocomial infections in the SICU. Of these patients, 64 had CAUTIs as defined in this study, and 162 met the criteria for the control group. Multivariate logistic regression analysis identified two risk factors independently associated to CAUTIs: the duration of having an indwelling catheter (OR = 1.014; 95% CI 1.005–1.024; p = 0.003) and female gender (OR = 2.377; 95%CI 1.278–4.421; p = 0.006). Overall 71 pathogens were isolated from the urine culture of 64 patients with CAUTIs. Candida spp. (28.2%), Pseudomonas aeruginosa (18.3%) and Klebsiella spp. (15.5%) were the most frequently isolated microorganisms. Conclusions. The risk factors and causative microrganisms considering CAUTIs in the SICU must be considered in of planning CAUTIs prevention in this setting.